Rapid turnover of functional sequence in human and other genomes. - Ponting, C; Nellåker, C; Meader, S (2011)
The amount of a genome's sequence that is functional has been surprisingly difficult to estimate accurately. This has severely hindered analyses asking whether the amount of functional genomic sequence correlates with organismal complexity. Most studies estimate these amounts by considering nucleotide substitution rates within aligned sequences. These approaches show reduced power to identify sequence that is aligned, functional, and constrained only within narrowly defined phyla. The neutral indel model exploits insertions or deletions (indels) rather than substitutions in predicting functional sequence. Surprisingly, this method indicates that half of all functional sequence is specific to individual eutherian lineages. This review considers the rates at which coding or noncoding and functional or nonfunctional sequence changes among mammalian genomes. In contrast to the slow rate at which protein-coding sequence changes, functional noncoding sequence appears to change or be turned over at rapid rates in mammals.